Augmented Reality (AR) Sebagai Media Interaktif Dalam Pembelajaran Bahasa Arab Di UIN Sunan Kalijaga Yogyakarta - Hidayat, Yusron; Sabarudin, Sabarudin; Mawardi, Ari Cahya (Mahira: Journal of Arabic Studies & Teaching, 2025)
This study aims to explore students’ experiences in using Augmented Reality (AR) as an innovative medium to enhance Arabic speaking skills (maharah al-kalām). Conducted with sixth-semester students of the Arabic Language Education Program at UIN Sunan Kalijaga Yogyakarta, the research applied a qualitative descriptive approach. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model. Findings indicate that AR improves comprehension of abstract concepts, supports vocabulary acquisition, and fosters students’ confidence and participation through 3D visualizations and contextual simulations. However, challenges include limited AR-based Arabic content, digital infrastructure, and technological readiness. The study highlights AR’s potential as a pedagogical tool in Islamic higher education, emphasizing the importance of teacher facilitation and interdisciplinary collaboration.